2021
DOI: 10.5222/terh.2021.23356
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of COVID-19 Pandemic on Pain, Physical Activity, and Anxiety in Individuals with Chronic Musculoskeletal Pain

Abstract: Objective: The COVID-19 pandemic has many features that can potentially trigger and increase chronic pain. The aim of this study was to examine the effects of the pandemic on pain, physical activity and anxiety in individuals with chronic musculoskeletal pain, in both periods of isolation and controlled social life. Methods: Seventy one individuals with chronic musculoskeletal pain were included in the study. Three different periods (pre-pandemic, isolation and controlled social life) were evaluated and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Thirteen studies with 13,372 participants evaluated the effects of COVID-19 on patients with varied chronic musculoskeletal pain conditions [2,8,25,[43][44][45][46][47][48][49][50][51][52]. The sample size ranged from 71 to 3502; 45-91% of patients were female.…”
Section: Other Musculoskeletal Disorders and Chronic Pain Syndromesmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen studies with 13,372 participants evaluated the effects of COVID-19 on patients with varied chronic musculoskeletal pain conditions [2,8,25,[43][44][45][46][47][48][49][50][51][52]. The sample size ranged from 71 to 3502; 45-91% of patients were female.…”
Section: Other Musculoskeletal Disorders and Chronic Pain Syndromesmentioning
confidence: 99%
“…Twelve of the 13 studies reported increased pain severity and disease activity during the pandemic [2,8,25,[43][44][45][46][48][49][50][51][52]. Decreased physical activity correlated to worsened pain in seven studies [2,8,25,[43][44][45][46][47][48][49][50][51][52].…”
Section: Other Musculoskeletal Disorders and Chronic Pain Syndromesmentioning
confidence: 99%
See 2 more Smart Citations